Nível de aceitação de risco em empresas de mobiliário: As visões dos técnicos de ST - Rodrigues, Matilde (2014)
The understanding of the level of occupational risk that stakeholders’ are able to accept is an important key to the entire risk management process, particularly in the definition of the acceptance criteria. However, researches about this issue relating to occupational risks are scarce. Therefore, this study aims to analyse the level of risk that Occupational, Safety & Health (OSH) professionals are willing to accept in the furniture sector. The accidents distribution of the sector was analysed. A questionnaire called Analysis of Risk Acceptance in the Furniture sector (ARAF) was developed and applied. The ARAF included two main parts. The first part referred to the professional characterization and second part included 15 questions, where each one was constituted by a set of risk scenarios, created with basis on the accidents distribution. Groups of OSH professionals with similar judgments were identified by means of a two-step cluster analysis. Three distinct groups were found: unacceptable, tolerant and realistic groups. The realistic group has identified the limit of tolerable risk close to the Cumulative Distribution Function curve of the furniture sector accident and the acceptable limit lower than this curve. This study shows that there are differences in the judgments of OSH professionals about the level of risk acceptance.